Peran Perempuan dalam menjaga Ketahanan Keluarga Masyarakat Bangkalan dengan Pedoman Hidup Rampka Naong Beringin Korong - Rifatul Firda Meinia; Mohammad Hipni (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
The family is the main environment which is an important group in the life of an individual or society as a whole. Family is a social unit consisting of individuals connected by ties of blood, marriage, or adoption who live together in the same house or environment. Among the important functions in the family are important roles and positions, such as the head of the household (father/husband) whose role is provider, protector and safeguard and other functions which are generally played by men. Likewise, women have a role as household managers, managing daily tasks at home, caring for children and families, participating in decisions,The role of women in maintaining peace can be central to family coordination in maintaining family integrity and welfare. This shows that women also have an important role in the family sphere. The resilience of a family requires quite in-depth attention because nowadays there are many cases that cause family resilience to be weakened due to inadequate handling of conflicts within the family as well as involvement in decision making so that this can affect family welfare or resilience within a family. . Another factor is also caused by a lack of attention or awareness of women regarding the role of their position and responsibilities. which is caused by environmental differences and mainly due to the principles or guidelines of life that they believe in. This can influence the values applied in maintaining family resilience. With so many structures in the family, a foundation is needed to maintain family resilience, which refers to the family's ability to survive, adapt and face various challenges and changes in life. Of course, this is not only the responsibility of the male head of the household or husband, but also requires women's involvement in maintaining family resilience. Women have a very significant contribution in maintaining the family in accordance with their values or life guidelinesThis research will discuss in more depth the role of women in family resilience, focusing more on the role of women in maintaining family resilience with the Rampak Naong Beringin Korong life guide which is a characteristic of Madurese society. This type of research method is descriptive, namely research that aims to provide an overview of a concept that can answer questions about the research subject. There were 4 interview subjects in this research, including women with formal and non-formal education as well as village and city women in the Bangkalan Madura area.